ADOLESCENT KNOWLEDGE OF SEXUAL ABUSE AMONG JUNIOR HIGH SCHOOL STUDENTS IN MEDAN - Prilda Roulyna Napitua; Rasmita, Dina (Nurse and Holistic Care, 2025)
Background: Sexual abuse remains a pressing concern among adolescents, particularly in Indonesia, where rising cases indicate both systemic and educational gaps. Adolescents are developmentally vulnerable and often lack the necessary knowledge to identify, resist, or report abusive behavior. Objective: This study aimed to assess the level of knowledge about sexual abuse among female adolescents attending a public junior high school in Medan, Indonesia. Methods: A descriptive quantitative design was employed, involving 106 female students selected from a population of 376 through proportionate stratified random sampling. Data were collected using validated questionnaires measuring demographic characteristics and knowledge of sexual abuse. The sexual abuse knowledge instrument consisted of 26 items, demonstrating strong internal consistency (Cronbach’s Alpha = 0.879). Data were analyzed using univariate analysis to determine frequency distributions. Result: The results revealed that 79.2% of respondents possessed good knowledge about sexual abuse, while 20.8% had sufficient knowledge. Most participants had received information from parents, schools, peers, and digital media. However, 21.7% reported having experienced sexual abuse, highlighting a significant gap between awareness and real-life prevention. Knowledge was highest regarding physical forms of abuse and lowest concerning non-verbal forms, such as inappropriate gestures or stares. Conclusion: Adolescents demonstrate generally good knowledge about sexual abuse; notable weaknesses persist in recognizing non-verbal abuse and translating awareness into protective behavior. These findings underscore the need for comprehensive, multi-source educational interventions emphasizing practical prevention skills and reporting mechanisms.